AUTOMATED LOS MONITORING FOR BTS TOWERS USING IOT-BASED IMAGING AND WEB INTERFACE - Heryanto, M Ary; Roziqin, Kusnur; Saputra, Wahyu; Hilmi, Fahriska; Arifin, Zaenal; Pambudi, Arga Dwi; Wulandari, Sari Ayu (National Standardization Agency of Indonesia, 2025)
The rapid growth of mobile telecommunication networks demands reliable Line of Sight(LoS) monitoring for BTS towers, as manual inspections are labor-intensive and risky.This study proposes an automated LoS monitoring system combining hardware andsoftware for safer, more accurate, and efficient operation. The system employs a 360°rotating camera on a BTS tower, controlled by Arduino Uno and Raspberry Pi 3B+, withdata transmitted via SIM7000E to a cloud server and accessible through a web-basedapplication. Experiments show a low average angular error of 1.65%, with systemstability validated using Bode plot, Root Locus, and Routh-Hurwitz methods. Resultsdemonstrate improved accuracy, reduced operational risks, and a scalable solution fortelecommunication infrastructure monitoring.